Black Chicago's First Century : 1833-1900 - Ferrell, Robert H. (Book collections on Project MUSE., 2006)
"Examines the personal styles of presidents Woodrow Wilson, Warren Harding, Calvin Coolidge, and Harry Truman. Uses the diaries of Colonel Edward House and White House physician Joel Boone and other sources to examine presidential decision making. Incorporates comments on Hoover and Franklin Delano Roosevelt. Includes interview with historian John Garraty"--Provided by publisher.